Spontaneous Convexity Subarachnoid Hemorrhage Caused by Internal Carotid Occlusion: Radiological Features - Pereira, Benedito Jamilson Araújo; de Holanda, Radmila Agra Cariry Targino; Targino Neto, José; de Holanda, Luciano Ferreira (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
A 79-year-old patient was admitted to the emergency room with transitory monoparesis in the left hand and dysphasia. The brain computed tomography (CT) and magnetic resonance imaging (MRI) showed a spontaneous right convexity subarachnoid hemorrhage (cSAH). Digital subtraction angiography (DSA) confirmed an asymptomatic occlusion of the right internal carotid artery (ICA) . Cases related to stenosis have already been described, but there is no similar report of a case related to occlusion, even though the pathophysiology of both entities is similar. Atraumatic SAH has been associated with intracranial and extracranial artery stenosis.
Keywords: spinal hemorrhage; carotid stenosis; skull tomography